(untitled) - Lung, C. W. (Singapore, 1999)
The book is intended to describe the basic and newly developed elements of the physics of solids and materials science on mechanical properties of metals with as much continuity as is possible. Particular emphasis has been placed in atomistic and fractal approaches and continuum theory of dislocations is also introduced. Since the book is meant for the two main topics of progress in recent years, some interesting and important topics which have not been discussed or introduced are given in detail.
Keywords: Metals,Kim loại